PENGARUH PENDAPATAN ASLI DAERAH DAN DANA BAGI HASIL TERHADAP BELANJA DAERAH PEMERINTAH KABUPATEN GIANYAR - Putu Citta Nirmala; Cokorda Gde Bayu Putra (UNHI Press, 2021)
This research was conducted at Gianyar Regency Goverment. The phenomenon that occurs is the ineffective use of Original Local (PAD) and Profit Sharing Funds (DBH) and Local Expenditure (BD) that are greater than Regional Revenues. The purpose of this study is to determine the effect of PAD and DBH against Local Expenditure in Gianyar Regency Government.. The method use in this research is the method and deskriptif verifikatif with quantitative approach. The research was conducted in 15 periods in the 2006 - 2020 fiscal year. Data analysis testing techniques in this study were assisted by IBM Statistics 23, carried out through the following stages: (1)classical assumption test, (2)multiple linear regression analysis, (3)coefficient of determination (4)and hypothesis testing with t test and f test. The result of this study found that Original Local Revenue (PAD) of the Gianyar Regency Government has a positive and statistically significant influence on the Regional Expenditure (BD) of the Gianyar Regency Government, while Profit Sharng Fund (DBH) of the Gianyar Regency Government has a positive but not statistically significant effect on the Local Expenditure (BD) of the Gianyar Regency Government.